2010
DOI: 10.1007/s11250-010-9654-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of tropical protein-rich leaves as supplements to Thai swamp buffalo receiving a basal diet of rice straw and treated leucaena (Leucaena leucocephala)

Abstract: Two experiments were conducted to determine (i) the effects of protein-rich trees (PRTs) and (ii) the effects of leucaena treated with NaOH solution and leucaena plus polyethylene glycol (PEG) on nutrient digestibility, nitrogen (N) balance, urinary purine derivatives excretion and blood metabolites in Thai swamp buffaloes. In Experiment 1, animals were fed with rice straw as a basal diet and one of the four PRT supplements: (i) oven-dried rain tree pods (RTPP, control); (ii) sun-dried leucaena leaves; (iii) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Leucaena is also known for its high nutritional value and acceptability and for its similar chemical composition to that of Alfalfa. The results found in this study are similar to those reported by several authors (Barcellos et al, 2008;Jetana et al, 2011). Differences between the Leucaena hybrid and Leucaena l. cv Cunningham were also reported by Barcellos (2006).…”
Section: Resultssupporting
confidence: 93%
“…Leucaena is also known for its high nutritional value and acceptability and for its similar chemical composition to that of Alfalfa. The results found in this study are similar to those reported by several authors (Barcellos et al, 2008;Jetana et al, 2011). Differences between the Leucaena hybrid and Leucaena l. cv Cunningham were also reported by Barcellos (2006).…”
Section: Resultssupporting
confidence: 93%
“…Multiple purpose trees, such as leucaena (Leucaena leucocephala), have proven to be effective by improving nutrient utilisation, leading to improving nutrient intakes (Majuva-Masafu and Linington 2006), nutrient digestibility and animal performance (Rubanza et al 2005) and lactation (Ghosh et al 2007) and also reduce the use of expensive concentrates (Jetana et al 2011). The farmers who raise buffaloes are not motivated to use this plant.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that none the different proportions of RTPP affects to PDs/DOMI ratios, but the high proportions of RTPP in leuceana increased mimosine + DHP in the urine, but did not beyond 100 mg/kg BW 0.75 . ); RTPP: Sun-dried rain tree pod pellet; 300 g RTPP: 300 g sun-dried rain tree pod pellet + 3.0 kg chopped fresh leucaena leaves; 600 g RTPP: 600 g sun-dried rain tree pod pellet + 3.0 kg chopped fresh leucaena leaves; 1,100 g RTPP: 1,100 g sun-dried rain tree pod pellet + 3.0 kg chopped fresh leucaena leaves; 1,600 g RTPP: 1,600 g sun-dried rain tree pod pellet + 3.0 kg chopped fresh leucaena leaves Source: Jetana et al (2011) The rain tree pod can be used as an appetizing material for combination with leaves of luecaena, mulberry and cassia. However, the RTPP dietary supplement containing high sugar enhanced microbial supply to the small intestine when fed to animals.…”
Section: Methodsmentioning
confidence: 99%
“…However, the microbial yield supply to the small intestine decreases in animals fed leucaena treated with NaOH diet, accordingly the NaOH treated leucaena may not only decrease the phenolic compounds and tannins, but also reduce N and water soluble carbohydrates contents (SundstØl & Owen 1984). Jetana et al (2011) As consequence of the condensed tannins contents, these are still the main problem, if leucaena leaves is used as feedstuff in ruminants. Both treatments of leucaena by adding PEG and treating with NaOH solution to control tannins results in increasing fibre digestion.…”
Section: Response Of Urinary Pds and The Ratios Pds/domimentioning
confidence: 99%
See 1 more Smart Citation